Вычислить а) lgtg1°·lgtg2°·lgtg3...lgtg88°·lgtg89 b)㏒ₐ㏒ₐ[latex] \sqrt[a]{ \sqrt[a]{... \sqrt[a]{x} } } [/latex] , все выражение под корнем равно 2008

Вычислить а) lgtg1°·lgtg2°·lgtg3...lgtg88°·lgtg89 b)㏒ₐ㏒ₐ[latex] \sqrt[a]{ \sqrt[a]{... \sqrt[a]{x} } } [/latex] , все выражение под корнем равно 2008
Гость
Ответ(ы) на вопрос:
Гость
a) lgtg1°·lgtg2°·lgtg3...lgtg88°·lgtg89 =  lgtg1°·lgtg2°·lgtg3....lgtg45°..lgtg88°·lgtg89 = lgtg1°·lgtg2°·lgtg3....lg1..lgtg88°·lgtg89 = lgtg1°·lgtg2°·lgtg3....0...lgtg88°·lgtg89  =0.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы